Pulley Reconstruction for Symptomatic Instability of the Tendons of the First Extensor Compartment Following de Quervain's Release - Renson, Daan; Mermuys, Koen; Vanmierlo, Bert; Bonte, Francis; Van Hoonacker, Petrus; Kerckhove, Diederick; Berghs, Bart; Goubau, Jean F. (Journal of Wrist Surgery, 2018)
Background Surgical management of de Quervain's tenosynovitis is based on decompression of the first extensor compartment. A simple release of the first compartment can cause instability of the extensor pollicis brevis (EPB) and abductor pollicis longus (APL) tendons in zone seven of the extensors. The WHAT test (wrist hyperflexion and abduction of the thumb) is very effective in diagnosing this instability.Patients and Methods In this retrospective monocentric study, we analyzed a case series of 10 patients all of whom underwent a reconstruction of the first extensor compartment using a retinacular graft because of symptomatic instability after decompression surgery. The reconstruction was a modified technique of the sixth compartment. Functional outcome and characteristics of the newly reconstructed pulley were examined by physical examination with the aid of ultrasound and internationally validated questionnaires.Results Four patients had a good-to-excellent functional outcome, all of those had a maximum of two surgical procedures performed on the first extensor compartment. Six patients presented poor functional outcome. In four of them, more than two surgical procedures were performed. Minor residual instability was noted in six cases, found in both the groups.Conclusion The reconstruction procedures on the first compartment seemed to be satisfactory in treating instability of the EPB and APL tendons after primary surgical release for de Quervain's disease.Level of Evidence Level IV, observational study without controls.
Keywords: de Quervain; tendon instability; WHAT test; pulley reconstruction; retinaculum